2020
DOI: 10.1111/mpp.12901
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas campestris sensor kinase HpaS co‐opts the orphan response regulator VemR to form a branched two‐component system that regulates motility

Abstract: Xanthomonas campestris pv. campestris (Xcc) controls virulence and plant infection mechanisms via the activity of the sensor kinase and response regulator pair HpaS/hypersensitive response and pathogenicity G (HrpG). Detailed analysis of the regulatory role of HpaS has suggested the occurrence of further regulators besides HrpG. Here we used in vitro and in vivo approaches to identify the orphan response regulator VemR as another partner of HpaS and to characterize relevant interactions between components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 54 publications
1
49
1
Order By: Relevance
“…The HK autophosphorylates its histidine residues via ATP hydrolysis and then transfers the phosphate group to the aspartate residues of the cognate RR to trigger adaptive responses (Stock et al, 2000). In Xanthomonas , five TCSs, namely, RpfC/RpfG (Stock et al, 2000), RavA/RavR (Tao et al, 2014), HpaS/HrpG (Li et al, 2014), HpaS/HpaR2 (Li et al, 2014), and HpaS/VemR (Li, Wang, et al, 2020), have been identified. RpfC/RpfG positively regulates the expression of extracellular enzymes and EPS, and negatively regulates intercellular c‐di‐GMP signal transduction (Stock et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HK autophosphorylates its histidine residues via ATP hydrolysis and then transfers the phosphate group to the aspartate residues of the cognate RR to trigger adaptive responses (Stock et al, 2000). In Xanthomonas , five TCSs, namely, RpfC/RpfG (Stock et al, 2000), RavA/RavR (Tao et al, 2014), HpaS/HrpG (Li et al, 2014), HpaS/HpaR2 (Li et al, 2014), and HpaS/VemR (Li, Wang, et al, 2020), have been identified. RpfC/RpfG positively regulates the expression of extracellular enzymes and EPS, and negatively regulates intercellular c‐di‐GMP signal transduction (Stock et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of hpaS or hrpG eliminates bacterial virulence and the hypersensitive response (HR) (Li et al, 2014). Similar to HpaS/HrpG, hpaS deletion reduces the phosphorylation level of the orphan RR VemR in vivo, and the HpaS/VemR TCS controls the swimming behaviour of Xcc (Li, Wang, et al, 2020). According to these studies, HpaS phosphorylates at least three RRs (HrpG, VemR, and HpaR2), but how and when HpaS interacts with these RRs needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal inhibitory concentration (MIC) method (Li et al, 2020 ) was employed to test the sensitivity of the Xcc strains to several environmental stresses. Xcc strains were cultured overnight and diluted to an OD 600 of 0.1.…”
Section: Methodsmentioning
confidence: 99%
“…EPS and extracellular enzyme assays were performed as previously described (Li et al, 2020 ; Tang et al, 1991 ). To estimate EPS production, Xcc strains were inoculated into 100 ml NY liquid medium containing glucose (2% wt/vol) at 28 °C, 200 rpm for 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation